# Equality of gcd's

Not what you're looking for? Search our solutions OR ask your own Custom question.

Show that if gcd(a, b) = 1, then gcd(ac, b) =gcd(b, c).

Â© BrainMass Inc. brainmass.com November 30, 2021, 1:09 am ad1c9bdddfhttps://brainmass.com/math/graphs-and-functions/equality-gcds-85988

#### Solution Preview

Proof:

Let x=gcd(ac,b), y=gcd(b,c).

First, since y=gcd(b,c), then y|b, y|c, so y|ac, thus y is a ...

#### Solution Summary

This solution is comprised of a detailed explanation to show that if gcd(a, b) = 1, then gcd(ac, b) =gcd(b, c).

$2.49